Esports research: Critical, empirical, and historical studies of competitive videogame play - Steinkuehler, C. (Games and Culture, 2020)
Despite the rise of esports over the last decade, to date there is little effort to coordinate research related to the subject. This special issue attempts to address this gap by presenting a diversity of research exemplars from scholars both within and outside the United States The articles included herein were culled from the top peer-reviewed papers presented at the first annual Esports Research Conference (https://uciesc.org) held October 2018 at the University of California, Irvine, attended by more than 200 academic researchers and esports industry professionals. Together, the collection of articles represents the range of theoretical, methodological, and thematic perspectives in contemporary esports research.